2007
DOI: 10.4049/jimmunol.179.8.5543
|View full text |Cite
|
Sign up to set email alerts
|

Hematin Promotes Complement Alternative Pathway-Mediated Deposition of C3 Activation Fragments on Human Erythrocytes: Potential Implications for the Pathogenesis of Anemia in Malaria

Abstract: Childhood malaria caused by Plasmodium falciparum is often characterized by severe anemia at low parasite burdens; the mechanism(s) responsible for this pathology remain to be defined. We have reported, based on clinical observations and in vitro models, that complement control proteins on erythrocytes such as CR1, the immune adherence receptor specific for C3b, may be reduced in childhood malaria, suggesting a possible role for complement in erythrocyte destruction. Intravascular lysis of iE by P. falciparum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 65 publications
5
76
0
Order By: Relevance
“…First, we found that the presence of heme in NHS is sufficient to trigger fluid phase complement AP activation with release of anaphylotoxins C3a and C5a, as well as sC5b9, in agreement with previous reports. 13,30 Heme has a dual role in complement, activating AP but inhibiting the binding of C1q to its ligands. 23 We investigated the mechanism of AP complement activation and showed that it results from the interaction of heme with the C3 molecule, which favors C3 homophilic interactions and leads to the formation of an active AP C3/C5 convertase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that the presence of heme in NHS is sufficient to trigger fluid phase complement AP activation with release of anaphylotoxins C3a and C5a, as well as sC5b9, in agreement with previous reports. 13,30 Heme has a dual role in complement, activating AP but inhibiting the binding of C1q to its ligands. 23 We investigated the mechanism of AP complement activation and showed that it results from the interaction of heme with the C3 molecule, which favors C3 homophilic interactions and leads to the formation of an active AP C3/C5 convertase.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Complement AP activation has also been reported during the acute phase of other hemolytic disorders, such as sickle-cell disease, 15 b thalassemia major, 16 and thrombotic thrombocytopenic purpura, 17 but the participation of hemoglobin or its breakdown products in complement activation has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…So via complement activation, free heme may perpetuate the development of anemia in patients with extravascular hemolysis. 38,39 In contrast, a negative effect of free heme on C1q binding to IgG and IgM has been described. 40,41 It was mentioned that classical pathway activation can be modulated by released heme by inhibiting the binding of C1q to its ligands.…”
Section: (See Above)mentioning
confidence: 99%
“…A variety of disorders may lead to formation of hemin, which in turn may drive erythrocytes into cell death [29,39,48,49,59,61,70]. On the other hand, hemin has been proven useful in the treatment of acute porphyria [62,63].…”
Section: Introductionmentioning
confidence: 99%